Regional development and criminality rate in Romania : insights from a spatial analysis - Zizi Goschin (Revista română de economie, 2017)
Although many recent studies have approached the topic of criminality, the regional dimension of the phenomenon is still under research. This paper employs a variety of statistical methods, from descriptive statistics to convergence and spatial econometrics, in an attempt to explore criminality rate in Romania, at county level, over 1990-2014. The analysis revealed that developed counties tend to have higher criminality rates, with Ilfov County and Bucharest Municipality frequently on top positions, and the county rankings are relatively stable in the short run. Against expectations, the regression models that have been estimated could not provide enough support for the GDP per capta (proxy for development level) as a statistically significant factor of influence on criminality rate in all years, but the explanatory variable criminality rate in previous year proved to be positive and highly significant in all models, indicating the relative inertia of this phenomenon.
2665773-9; 2344-4657; Revista română de economie; 717197875